Inclusion by live streaming? Contested meanings of well-being: movement and non-movement of space, place and body. Issue 4 (4th July 2019) - Rautiainen-Keskustalo, Tarja; Raudaskoski, Sanna
ABSTRACT: The article explores how the ideological discourses and practical actions that aim to increase well-being by means of art are possible to understand from the point of view of different kinds of mobilities and immobilities. An empirical case of a concert series live streamed to seniors and prison inmates by a concert hall is examined. The concerts aimed to enhance cultural inclusion, but in practice, live streaming highlighted the complexity of the network, where social spaces, places and bodily resources of the individuals were negotiated through movement and non-movement.